Risk Factors for Throwing-Related Shoulder and Elbow Pain in Adolescent Baseball Players: A Prospective Study of Physical and Developmental Factors. Issue 9 (17th September 2021) - Tajika, Tsuyoshi; Oya, Noboru; Kuboi, Takuro; Endo, Fumitaka; Ichinose, Tsuyoshi; Shimoyama, Daisuke; Sasaki, Tsuyoshi; Hamano, Noritaka; Omodaka, Takuya; Kobayashi, Hiroki; Mieda, Tokue; Okamura, Koichi; et al.
Background: Throwing-related shoulder and elbow pain continues to be reported among adolescent baseball players. Few prospective studies have specifically examined the association between throwing-related shoulder and elbow pain and physical and developmental changes. Purpose: To evaluate the changes in physical and developmental characteristics during 1 year with respect to throwing-related shoulder and elbow pain in adolescent baseball players. Study Design: Case-control study; Level of evidence, 3. Methods: This 1-year prospective follow-up study investigated 164 baseball players aged 7 to 13 years. Player data (age, height, weight, field position, and pitch count), lower extremity muscle tightness, and range of motion (ROM) of the shoulder, elbow, and hip joints were assessed during the 2016 and 2017 preseason medical examinations. After the 2016 season, the participants completed questionnaires related to throwing-related shoulder and elbow pain, defined as an inability to play for ≥1 week because of elbow or shoulder difficulties. For study participants with and without throwing-related shoulder or elbow pain during the 2016 season, we conducted univariate and multivariate logistic regression analysis to identify risk factors for throwing-related shoulder or elbow pain. Results: Overall, 21 players (12.8%) reported a shoulder pain episode, 56 players (34.1%) had an elbow pain episode, and 70 players (42.7%) reported having experienced shoulder and/or elbow pain during the 2016 season. In multivariate logistic regression analysis, (1) shoulder pain was associated with 2016 preseason height (odds ratio [OR], 1.06; 95% CI, 1.01-1.11; P = .01) and change in dominant-side elbow extension ROM from 2016 to 2017 (OR, 1.12; 95% CI, 1.02-1.24; P = .02); (2) elbow pain was associated with change in weight from 2016 to 2017 (OR, 1.21; 95% CI, 1.04-1.41; P = .014); and (3) throwing-related shoulder and/or elbow pain was associated with greater 2016 preseason height (OR, 1.04; 95% CI, 1.003-1.68; P = .03) and an increase in height from 2016 to 2017 (OR, 1.17; 95% CI, 1.01-1.35; P = .03). Conclusion: Our results indicated that adolescent baseball players who were taller in the preseason and those with an increase in height over the 1-year study period faced significant risks for developing throwing-related shoulder and/or elbow pain.